The Extended Evolutionary Synthesis and Thomistic Metaphysics. Comments on Mariusz Tabaczek’s Theistic Evolution - Kuebler, Daniel (Theology and science, 2025)
In the past few decades, our understanding of evolution has been enriched by the development of the Extended Evolutionary Synthesis (EES). In general, the EES has highlighted the active role of the organism in the evolutionary process as opposed to older reductionist gene-centric approach. This emerging view of evolution appears much more compatible with Thomistic metaphysics, largely because it refocuses the process of evolution in terms of the inherent powers of organisms. In addition, the ubiquity of evolutionary convergence seems to point to the underlying potentiality of physical matter as playing an important role in the evolution of biological forms.